The After Christmas Tree - Welby, Bethan (London : Scallywag Press Ltd, 2020)
On a cold afternoon in January, Brian sees a little Christmas tree, stripped of its decorations and discarded by the roadside. He immediately decides to take it home with him and look after it...but will it be as easy as he thinks, and will his family be pleased?
Commended for Klaus Flugge Prize 2021
Keywords: Christmas trees -- Pictorial works -- Juvenile fiction; Responsibility in children -- Pictorial works -- Juvenile fiction; Families -- Pictorial works -- Juvenile fiction; Christmas fiction